Enhancing the Dendrite Tolerance of NaSICON Electrolytes by Suppressing Edge Growth of Na Electrode along Ceramic Surface. Issue 40 (23rd August 2022) - Ma, Qianli; Ortmann, Till; Yang, Aikai; Sebold, Doris; Burkhardt, Simon; Rohnke, Marcus; Tietz, Frank; Fattakhova‐Rohlfing, Dina; Janek, Jürgen; Guillon, Olivier
Abstract: Solid‐state sodium batteries (SSNBs) have attracted extensive interest due to their high safety on the cell level, abundant material resources, and low cost. One of the major challenges in the development of SSNBs is the suppression of sodium dendrites during electrochemical cycling. The solid electrolyte Na3.4 Zr2 Si2.4 P0.6 O12 (NZSP) exhibits one of the best dendrite tolerances of all reported solid electrolytes (SEs), while it also shows interesting dendrite growth along the surface of NZSP rather than through the ceramic. Operando investigations and in situ scanning electron microscopy microelectrode experiments are conducted to reveal the Na plating mechanism. By blocking the surface from atmosphere access with a sodium‐salt coating, surface‐dendrite formation is prevented. The dendrite tolerance of Na | NZSP | Na symmetric cells is then increased to a critical current density (CCD) of 14 mA cm −2 and galvanostatic cycling of 1 mA cm −2 and 1 mAh cm −2 (half cycle) is demonstrated for more than 1000 h. Even if the current density is increased to 3 mA cm −2 or 5 mA cm −2, symmetric cells can still be operated for 180 h or 12 h, respectively. Abstract : Fast Na‐dendrite growth along the surface of Na3.4 Zr2 Si2.4 P0.6 O12 (NZSP) rather than through the ceramic is observed. Atmosphere and surface‐coating influence the surface‐dendrite growth on NZSP. After coating the NZSP surface with a protective layer, the critical current density of the Na | NZSP | Na symmetric cells increases up to 14 mA cm −2 . The cell withstands galvanostatic cycling with 1 mA cm −2 and 1 mAh cm −2 for 1000 h.